2010
DOI: 10.1063/1.3487737
|View full text |Cite
|
Sign up to set email alerts
|

Atomic imaging of the monolayer nucleation and unpinning of a compound semiconductor surface during atomic layer deposition

Abstract: The reaction of trimethyl aluminum on the group III rich reconstructions of InAs(0 0 1) and In(0.53)Ga(0.47)As(0 0 1) is observed with scanning tunneling microscopy/spectroscopy. At high coverage, a self-terminated ordered overlayer is observed that provides the monolayer nucleation density required for subnanometer thick transistor gate oxide scaling and removes the surface Fermi level pinning that is present on the clean InGaAs surface. Density functional theory simulations confirm that an adsorbate-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 43 publications
(60 reference statements)
0
33
0
Order By: Relevance
“…Since a main difference between recipes A and B is the additional pumping/purging steps in B, we may conclude that these steps result in improved nucleation. Improved nucleation and growth of HfO 2 on III-V surfaces using small amounts of TMA either before or during deposition has been shown previously; [24][25][26] hence the additional pumping/purging steps likely result in a more uniform distribution of the nucleation centers generated by TMA-exposure of the surface, due to the additional time for surface diffusion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since a main difference between recipes A and B is the additional pumping/purging steps in B, we may conclude that these steps result in improved nucleation. Improved nucleation and growth of HfO 2 on III-V surfaces using small amounts of TMA either before or during deposition has been shown previously; [24][25][26] hence the additional pumping/purging steps likely result in a more uniform distribution of the nucleation centers generated by TMA-exposure of the surface, due to the additional time for surface diffusion.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of different implementations of the cleaning procedure showed that improving surface coverage is critical for significant D it reduction and EOT scaling. Both TMA and N are essential for providing nucleation sites that facilitate the growth of HfO 2 on In 0.53 Ga 0.47 As surfaces, 14,[24][25][26] and both species were detected at the interface in XPS and SIMS. The present study shows that optimization of the pre-deposition cleaning procedure, such as sequences and exposure times, are needed for a high density of these nucleation sites, and can enable very low-D it and highly scaled gate stacks.…”
Section: Discussionmentioning
confidence: 99%
“…22 However, most of the studies were focused on Si surfaces and less is known about the TMA/H 2 O reaction with Ge or III-V compound materials. 19,23,24 In addition, the direct reaction of TMA with Si or Ge has not been previously studied since it requires clean (oxygen-free and carbon-free) semiconductor surfaces in a water-free ALD reaction chamber. An extremely clean semiconductor surface can be formed in ultrahigh vacuum (UHV) conditions providing a unique opportunity to study the reactions of H 2 O and TMA on a semiconductor surface in a slow, step-wise fashion, while a typical ALD process is performed at 0.1∼100 Torr but with very fast processing.…”
Section: Introductionmentioning
confidence: 99%
“…Various in situ and in vacuo techniques provide the optimal means to explore these reactions. Techniques of interest include synchrotron x ray analysis, 114,115 x ray photoelectron measurements, 116 quartz crystal microbalance analysis, 117 Fourier transform infrared spectroscopy, 118 scanning probe microscopy, 119 ellipsometry, and transmission electron microscopy 120 as well as electrical properties analysis. 121 These measurements will provide complementary information about the surface reactions and molecular processes of the ALD on the substrates, which in turn will help identify the right ALD process conditions for the desired materials and interfacial properties.…”
Section: Discussionmentioning
confidence: 99%